Late Onset Systemic Lupus Erythematosus Manifests As Lupus Nephritis, A Rare Presentation - Pakeerathan, A.; Sujanitha, V.; Selvaratnam, G.; Pradeepan, J.A.; Brammah, R.T. (The Jaffna Medical Association, 2024)
Systemic lupus erythematosus(SLE) is a chronic, multisystemic autoimmune disorder typically affecting middle-aged individuals predominantly in women. Late-onset SLE occurs in individuals over 50, differs from classic SLE in terms of age, symptoms, organ involvement and severity. This case describes an elderly South-Asian woman who was under evaluation for skin rashes with impaired renal function, diagnosed to have discoid lupus with lupus nephritis(LN). She was treated with glucocorticoids and mycophenolate mofetil effectively, with improved renal function, thus delaying the need for dialysis. This case emphasizes timely diagnosis and treatment can significantly improve the outcome in late onset SLE with lupus nephritis(LN).
Keywords: South Asian woman; Discoid lupus; Lupus nephritis; Late-onset SLE